Exilic (Art) Narratives of Queer Refugees Challenging Dominant Hegemonies - Holle, Fabian; Rast, Maria Charlotte; Ghorashi, Halleh (Frontiers in Sociology, 2021)
Within the Dutch hegemonic discourse, the “migrant other” is portrayed as almost incompatible with “national culture” while it is simultaneously pressured to assimilate. This creates paradoxes for the queer refugee participants in this study. When these refugees assimilate, they risk reinforcing the dominant discourse considering their group as the “backward other”. When they do not assimilate, they are considered not “properly” Dutch. This paper explores how queer refugee artists can unsettle such dominant exclusionary discourses through exilic (art) narratives. Their experiences of exilic positioning (being neither there nor here) and queer liminality (e.g., nonbinary gender identifications) and their intersectional positionalities situate these artists in various “states of in-betweenness”. Although these states may be challenging, this paper shows how they can also stimulate agency. Inspired by a feminist approach, this study aimed to co-create knowledge with rather than about participants, focusing on creativity and resilience. Methods included biographical interviews and an arts-informed component in which participants were invited to create artistic works concerning their experiences during COVID-19 for an online platform. This study shows how the research participants challenge hegemonic discourses at various levels, using multiple modes of reflection and creation while engaging with their in-between situatedness. At the individual level, they challenge discourses by exploring (or performing) their non-conforming queer positioning through their art practices. At the communal level, plural reflexivity is triggered via art shared within and outside the community. At the societal level, queer refugees exercise activism creatively through images, songs or performances.